PENAMBAHAN INTERVENSI JAW’S EXERCISE PADA TRAKSI OSILASI SAMA BAIKNYA DENGAN TRAKSI OSILASI SAJA DALAM MENURUNKAN DISABILITAS DAN MENINGKATKAN MOBILITAS PADA KASUS TEMPOROMANDIBULAR JOINT DISCUS INTERNAL DERANGEMENT (Fisioterapi : Jurnal Ilmiah Fisioterapi, 2018)
To find out about difference addition of jaw’s exercises intervention on traction oscillate just as good with traction oscillate in decrease disability and improve mobility in the case of TMJ internal derangement. This research is experimental, the sample was selected based on purposive sampling technique.The control group given oscilate traction, treatment groups given jaw's exercise and oscilate traction.Treatment group on measuring instrument before TDI 34,1667±12,61 and after 17,083±6.96 and on measuring Caliper before 2,52±0.36 and after 3.36±0.42.whereas in the control group using a measuring instrument TDI 34,13±7.63 and after 14,1667±4.91 on caliper before 3,43±0.75 and after 4.15±0.46. Normality test with the Shapiro wilk test data obtained normal while its homogeneity test with Levene's test in homogeneous data. The results of hypothesis I and II with paired sample t-test, test hypothesis I retrieved the value pdisability=0,017 and pmobility=0.006, test the hypothesis II= Pvalue 0.000 (P< 0.001)test hypothesis III with independent sample t-test demonstrated the value of p (disability)= 0.138,p (mobility)=0.157. The addition of jaw’s exercises intervention on oscillate traction just as good with oscillate traction in decrease disability and improve mobility in the case of temporomandibular joint discus internal derangement. Keywords: Temporomandibular Joint, Jaw’s Exercise, Traction Oscillate